2017
DOI: 10.5539/ells.v7n1p36
|View full text |Cite
|
Sign up to set email alerts
|

The Soft Power of Teacher’s Instructional Decision Making: An Empirical Study of 4 Chinese EFL Teachers and Native English Teachers

Abstract: Beliefs, concepts and perceptions drive teachers' practices. This study reports a comparative enquiry into the soft power of decision making of two categories of teachers when approaching teaching in the language classroom. Decisions of tasks and participation structures teachers adopted in their instructions, and the underlying soft power of decision making in class are identified with reference to beliefs, knowledge, prior experiences and context. And it reveals that these teachers tend to capitalize on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…equity-oriented (Zhang and Yang, 2017). In a similar vein, the findings of one mixed study showed that although EFL teachers self-reported that they recognized equity as one of the most fundamental guidelines to achieve social justice when interacting with students in the classroom, they were subject to strong biases in terms of students' genders, personalities, social backgrounds, and English-speaking abilities (Chen, 2020).…”
Section: Empirical Studies Concerning the Interrelation Between Equit...mentioning
confidence: 97%
See 1 more Smart Citation
“…equity-oriented (Zhang and Yang, 2017). In a similar vein, the findings of one mixed study showed that although EFL teachers self-reported that they recognized equity as one of the most fundamental guidelines to achieve social justice when interacting with students in the classroom, they were subject to strong biases in terms of students' genders, personalities, social backgrounds, and English-speaking abilities (Chen, 2020).…”
Section: Empirical Studies Concerning the Interrelation Between Equit...mentioning
confidence: 97%
“…Notably, the mismatch in question here, which has become quite serious, lies in the fact that although teachers report that they have adopted a student-centered stance, they act in precisely the opposite way during their teaching. In an empirical qualitative study investigating four Chinese EFL teachers’ instructional decision making, the findings showed that although teachers intended to build an active and fair environment for all, their actual teaching was still teacher-centered rather than equity-oriented ( Zhang and Yang, 2017 ). In a similar vein, the findings of one mixed study showed that although EFL teachers self-reported that they recognized equity as one of the most fundamental guidelines to achieve social justice when interacting with students in the classroom, they were subject to strong biases in terms of students’ genders, personalities, social backgrounds, and English-speaking abilities ( Chen, 2020 ).…”
Section: Empirical Studies Concerning the Interrelation Between Equit...mentioning
confidence: 99%